BMMSC-derived Exosomes Attenuate Cardiopulmonary Bypass-related Acute Lung Injury by Reducing Inflammatory Response and Oxidative Stress - Zhang, Tao-Yuan; Zhang, Hui; Deng, Jing-Yu; Gong, Hai-Rong; Yan, Yun; Zhang, Zheng; Lei, Chong (Current Stem Cell Research & Therapy, 2023)
Background: Acute lung injury (ALI), which is characterized by inflammation and oxidative stress, is a common complication after cardiopulmonary bypass (CPB). Exosomes from bone marrow mesenchymal stem cells (BMMSC-Exo) have recently been identified as promising treatments for ALI. However, the effects of BMMSC-Exo on inflammation and oxidative stress in CPB-related ALI remain unclear. Objective: We aim to evaluate the effects of BMMSC-Exo on post-CPB ALI and explore their potential mechanisms. Methods: We randomly divided rats into three groups: sham, ALI, and ALI+BMMSC-Exo groups. Histological changes were evaluated by lung histo-pathology and bronchoalveolar lavage fluid (BALF). ELISA assay was used to determine inflammatory cytokine levels and oxidative stress. Results and Discussion: BMMSC-Exo attenuated histological changes (including the invasion of inflammatory cells), reduced the wet/dry (W/D) weight ratio, and downregulated inflammatory cytokine levels, including tumor necrosis factor-alpha (TNF-α), interleukin (IL)-6, and IL-1β. BMMSC-Exo also alleviated oxidative stress. In vitro, we further administered lipopolysaccharide (LPS) to alveolar macrophages (AMs) to mimic the pathological changes of ALI and found that BMMSC-Exo suppressed reactive oxygen species (ROS) production and downregulated the levels of inflammatory cytokines. Mechanistically, BMMSC-Exo inhibited the phosphorylation of nuclear factor-ΚB (NF-ΚB), the nuclear translocation of p65, also facilitated the phosphorylation of Akt and the nuclear translocation of Nrf2, while upregulating the expression of HO-1. Conclusion: In summary, we indicate that BMMSC-Exo reduces CPB-related ALI by alleviating inflammation and oxidative stress. The underlying mechanism may involve the NF-ΚB p65 and Akt/Nrf2/HO-1 signaling pathways.
Keywords: exosomes